Social movements and communication network an approach from the mobilization of young peruvians against the “Pulpin” Law - Acevedo Rojas, Jorge (2015)
The article explores and analyzes the role of digital communication networks, as well as instrument and social spaces for build wills, during the social mobilization against the law called “Pulpín”, between December 2014 and January 2015. The law was promoted by economic groups with government’s support, in order to promote access to the labor market to young people, but it raised social protest, because the law removed some labor rights. Thousands of young people and other social groups marched through streets and squares of Lima and other cities, and developed an intensive use of digital communication networks to coordinate, convene and express their points of view about the law and policies to promoteemployment, and also they achieved a significant presence in the media, becoming a social actor with capacity for political dialogue.